Current EU research activities on combined exposure to multiple chemicals. (November 2018) - Bopp, Stephanie K.; Barouki, Robert; Brack, Werner; Dalla Costa, Silvia; Dorne, Jean-Lou C.M.; Drakvik, Paula E.; Faust, Michael; Karjalainen, Tuomo K.; Kephalopoulos, Stylianos; van Klaveren, Jacob; Kolossa-Gehring, Marike; Kortenkamp, Andreas; et al.
Abstract: Humans and wildlife are exposed to an intractably large number of different combinations of chemicals via food, water, air, consumer products, and other media and sources. This raises concerns about their impact on public and environmental health. The risk assessment of chemicals for regulatory purposes mainly relies on the assessment of individual chemicals. If exposure to multiple chemicals is considered in a legislative framework, it is usually limited to chemicals falling within this framework and co-exposure to chemicals that are covered by a different regulatory framework is often neglected. Methodologies and guidance for assessing risks from combined exposure to multiple chemicals have been developed for different regulatory sectors, however, a harmonised, consistent approach for performing mixture risk assessments and management across different regulatory sectors is lacking. At the time of this publication, several EU research projects are running, funded by the current European Research and Innovation Programme Horizon 2020 or the Seventh Framework Programme. They aim at addressing knowledge gaps and developing methodologies to better assess chemical mixtures, by generating and making available internal and external exposure data, developing models for exposure assessment, developing tools for in silico and in vitro effect assessment to be applied in a tiered framework and for grouping of chemicals, as well as developing joint epidemiological-toxicological approaches for mixture risk assessment and for prioritising mixtures of concern. The projects EDC-MixRisk, EuroMix, EUToxRisk, HBM4EU and SOLUTIONS have started an exchange between the consortia, European Commission Services and EU Agencies, in order to identify where new methodologies have become available and where remaining gaps need to be further addressed. This paper maps how the different projects contribute to the data needs and assessment methodologies and identifies remaining challenges to be further addressed for the assessment of chemical mixtures. Highlights: Mapping EU funded research projects to different aspects of mixture risk assessment. Overview of current status and methodological developments Need to further address data and knowledge gaps overarching different chemical sectors